PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN (Studi Pada Alpha Hotel Pekanbaru) - Irham Pratama Putra; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the influence of situational leadership style and work motivation on employee job satisfaction (study on Alpha Hotel Pekanbaru). Situational leadership style as Variable (X1), Work Motivation as Variable (X2) and Job Satisfaction as a variable (Y).The method in this research is quantitative with SPSS program, where the samples used are employees of Alpha Hotel Pekanbaru that is as much as 56 respondents. In accordance with opinion (Roscoe, 2009) that the appropriate size in the study is 30 to 500. That number can already represent the population. Technique of collecting data through questionnaire.The result of this research conclude that situational leadership style variable and work motivation have significant influence to employee's job satisfaction Alpha Hotel Pekanbaru.Keyword: situational leadership, work motivation, employee job statisfication